Fossil parasites - De Baets, Kenneth 1984-; Littlewood, D. Timothy J. 1961- (Advances in parasitology, 2015)
Fossil Parasites, the latest edition in the Advances in Parasitology series established in 1963, contains comprehensive and up-to-date reviews on all areas of interest in contemporary parasitology, including medical studies of parasites of major influence, such as plasmodium falciparum and trypanosomes. The series also contains reviews of more traditional areas, such as zoology, taxonomy, and life history, which help to shape current thinking and applications. Parasitism is a dominant life history strategy and we know it has existed for millions of years. Detecting parasitism in the fossil record is problematic because we rarely see direct evidence and usually must rely on indirect evidence to infer its existence. This unique volume takes a broad and systematic view of direct and indirect evidence for parasitism in the fossil record